The Influence Of The Work Environment On Employee Work Motivation At PT. Loka Indah Lestari Pohuwato - Ahmad Nawawi; Abd. Rahman Pakaya; Endi Rahman (Jambura Science of Management, 2020)
The research aimed to find out to what extent the effect of work environment on work motivation. The population of this research was all 74 permanent employees at PT. Loka Indah Lestari in Popayato Barat, Pohuwato. The analysis method used simple linear regression analysis. The result of analysis revealed that the work environment had a significant effect on work motivation from tcount 3,975 > ttable 1,666 with a significance level of 0,000 < 0,05. Thus, it found that work environment affected work motivation for 39,2% or it was low effect between work envornment on work motivation, and it certainly contained a phenomenon of lack of company attention to employees related to the work environment, particuraly inadequate road access and communication media (signal). Meanwhile, simultaneously work environment had a significant effect on work motivation through the test of R-value coefficient model, namely 0,424, which meant a strong relationship. In addition, the value of R square was 0,180 or 18% whereas the rest 0,820 or 82% was affected by relationship with other factors out of this research.